2014
DOI: 10.1371/journal.pone.0100055
|View full text |Cite
|
Sign up to set email alerts
|

Pri-miR-124 rs531564 and pri-miR-34b/c rs4938723 Polymorphisms Are Associated with Decreased Risk of Esophageal Squamous Cell Carcinoma in Chinese Populations

Abstract: MicroRNAs are a new class of small non-protein-coding RNAs that sometimes function as tumor suppressors or oncogenes. Aberrant expression and structural alteration of microRNAs have been reported to be involved in tumorigenesis and cancer development. Recently, rs531564/pri-miR-124-1, rs4938723/pri-miR-34b/c, rs7372209/pri-miR-26a-1, rs895819/pre-miR-27a, and rs11134527/pri-miR-218 were reported to be associated with risks of various cancers. In order to evaluate the relationship of these SNPs and esophageal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…Based on the selection criteria above, five case-control studies (13)(14)(15)(16)(17) were finally enrolled in the meta-analysis with publication years that ranged from 2011 to 2014. The detailed literature retrieval process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the selection criteria above, five case-control studies (13)(14)(15)(16)(17) were finally enrolled in the meta-analysis with publication years that ranged from 2011 to 2014. The detailed literature retrieval process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4,763 subjects were involved in the meta-analysis, including 2,253 cancer cases and 2,510 healthy controls. Multiple cancer types were analyzed in the studies, including triple-negative breast cancer (13), cervical cancer (15) and ESCC (14,(16)(17). The diagnoses of these tumors were confirmed by histological or histopathological examinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al (23) found no significant association between the pri-miR-34b/c rs4938723 variant and esophageal squamous cell carcinoma (ESCC) in Kazakh patients in northwest China. However, Zhang et al (24) reported that pri-miR-34b/c rs4938723 significantly decreased the risk of ESCC in Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…miR-34a is encoded by its own transcript, while miR-34b and miR-34c share a common primary transcript (pri-miR-34b/c) (9). The promoter region of miR-34b/c transcripts contains p53-binding sites (22 Numerous studies investigated the impact of miR-34b/c rs4938723 on the risk of various cancers, but the results are inconsistent (19,(23)(24)(25)(26)(27)(28)(29)(30)(31). To the best of our knowledge, there is only one previous study regarding the impact of the miR-34b/c variant on BC risk (32).…”
Section: Introductionmentioning
confidence: 99%